Positron–electron correlation‐polarization potential model for positron binding in polyatomic molecules. Issue 17 (30th March 2020) - Sugiura, Yutaro; Suzuki, Haruya; Otomo, Takuma; Miyazaki, Takaaki; Takayanagi, Toshiyuki; Tachikawa, Masanori
Abstract: Positron binding energies (PBEs) of 41 polyatomic molecules were calculated using the positron–electron correlation‐polarization potential (CPP) approach and compared with experimentally measured values. In this approach, the short‐range positron–electron potential is modeled using the density‐functional expression, whereas the long‐range potential is approximated by the attractive polarization potential. The positron–electron CPP model based on local‐density approximation yields larger PBEs than experimental values; however, the calculated values can be substantially improved by introducing generalized gradient approximation. We also investigated the conformational dependence of PBEs for representative molecules. Abstract : Positron binding energies of 41 polyatomic molecules were calculated using the positron–electron correlation‐polarization potential approach, in which the short‐range positron–electron potential was described using the density‐functional expression. From the comparison of theory and experiment, we find that the calculated values can be improved by introducing generalized gradient approximation.